Hyperparasitaemic human Plasmodium knowlesi infection with atypical morphology in peninsular Malaysia - Lee, W.C.; Chin, P.W.; Lau, Y.L.; Chin, L.C.; Fong, M.Y.; Yap, C.J.; Supramaniam, R.R.; Mahmud, R. (2013)
Plasmodium knowlesi is a potentially life-threatening zoonotic malaria parasite due to its relatively short erythrocytic cycle. Microscopic identification of P. knowlesi is difficult, with "compacted parasite cytoplasm" being one of the important identifying keys. This report is about a case of hyperparasitaemic human P. knowlesi infection (27 parasitaemia) with atypical amoeboid morphology. A peninsular Malaysian was admitted to the hospital with malaria. He suffered anaemia and acute kidney function impairment. Microscopic examination, assisted by nested PCR and sequencing confirmed as P. knowlesi infection. With anti-malarial treatment and several medical interventions, patient survived and recovered. One-month medical follow-up was performed after recovery and no recrudescence was noted. This case report highlights the extreme hyperparasitaemic setting, the atypical morphology of P. knowlesi in the patient's erythrocytes, as well as the medical interventions involved in this successfully treated case.